A Dose Response Association Between Body Mass Index and Mortality in Patients with Peripheral Artery Disease: A Meta-analysis Including 5 729 272 Individuals. (March 2022) - Lin, Donna S.-H.; Lo, Hao-Yun; Yu, An-Li; Lee, Jen-Kuang; Yang, Wei-Shiung; Hwang, Juey-Jen
Abstract : Objective: Obesity is a significant risk factor for atherosclerotic cardiovascular disease; however, the "obesity paradox", in which obese patients enjoy superior survival, has been observed in various cardiovascular conditions. Whether this phenomenon exists for peripheral artery disease (PAD) remains uncertain. The goal of this study was to evaluate the relationship between body mass index (BMI) and mortality in patients with PAD. Methods: A comprehensive literature search identified seven eligible cohort studies that reported the association between BMI and all cause mortality in patients with PAD. A dose response meta-analysis was done for all cause mortality, short term (30 day or in hospital) mortality and long term mortality. The dose response association between BMI and mortality was also assessed in patients who received endovascular therapy (EVT). Results: The non-linear dose response analysis showed that higher BMI values were associated with a lower mortality risk from the range between 15 kg/m 2 to approximately 33 – 34 kg/m 2 . The risk of mortality increased slightly thereafter. This relationship was consistent with that of long term mortality but was not apparent in short term mortality. A U shaped relationship was also observed between BMI and mortality in patients who received EVT with the lowest mortality observed at around 30 kg/m 2 . Conclusion: The obesity paradox was evident in the analysis of long term survival among patients with PAD, with the lowest mortality rates observed in obese patients. However, this association was not observed for short term or in hospital mortality.